The Circumestellar Disk of the B0 Protostar Powering the HH 80-81 Radio Jet - Girart, J. M. (2017)
We present subarcsecond angular resolution observations carried out with the Submillimeter Array (SMA) at 880 μm centered at the B0-type protostar GGD27 MM1, the driving source of the parsec scale HH 80-81 jet. We constrain its polarized continuum emission to ≲0.8% at this wavelength. Its submillimeter spectrum is dominated by sulfur-bearing species tracing a rotating-disk-like structure (SO and SO2 isotopologues mainly), but also shows HCN-bearing and CH3OH lines, which trace the disk and the outflow cavity walls excavated by the HH 80-81 jet. The presence of many sulfurated lines could indicate the presence of shocked gas at the disk's centrifugal barrier or that MM1 is a hot core at an evolved stage. The resolved SO2 emission traces the disk kinematics very well and we fit the SMA observations using a thin-disk Keplerian model, which gives the inclination (47°), the inner (≲170 au) and outer (∼950-1300 au) radii, and the disk's rotation velocity (3.4 km s-1 at a putative radius of 1700 au). We roughly estimate a protostellar dynamical mass of 4-18 . MM2 and WMC cores show, comparatively, an almost empty spectra, suggesting that they are associated with extended emission detected in previous low-angular resolution observations, and therefore indicating youth (MM2) or the presence of a less massive object (WMC).